Analisis Yuridis Pembukaan Rahasia Bank Sebagai Upaya Pemberantasan Tindak Pidana Korupsi - Sari, Dewi Arnita; Sukaldi, Sukaldi (Institut Agama Islam Negeri Bone, 2022)
Dewi Arnita Sari and Sukaldi, Juridical Analysis of Bank Secrecy as an Effort to Eradicate Corruption The purpose of this study are: 1. To find out the application of bank secrets to the practice of criminal acts of corruption in Gorontalo Regency, 2. To find out what are the obstacles for law enforcers in opening bank secrets as an effort to eradicate Corruption Crime This research is a descriptive study with an empirical juridical approach. The research method used is a method using primary and secondary data with data collection techniques namely interviews and questionnaires. The population of this study was the entire Limbooto District Prosecutor's Office and the Society. The sample in this study was determined by 5 respondents using Purposive sampling techniques. The results of this study indicate that (1). The application of bank secrecy in eradicating corruption by prosecutors at the District Prosecutor's Office of Limbotodi runs optimally in accordance with legislation but is still considered difficult for law enforcers because in criminal justice must obtain permission from several elements while in civil cases do not require permission anymore to open bank secrets. Not all corruption cases apply the opening of bank secrets, the opening of bank secrets is not done when the suspects admit / justify what is alleged. (2) constraints for law enforcers in the opening of bank secrets as a legal factor, namely rules that limit their authority, law enforcement factors that are law enforcement officers who are dishonest, community factors namely lack of public awareness to report as a form of caring for corruption eradication, facilities and infrastructure, legal cultural factors, namely legal culture will be accepted by the community if the laws, regulations, and policies correspond to the culture of the community. The recommendations of this study are for requests for permits to obtain information from the bank on a criminal case that is processed at all levels outside the general court and special judiciary carried out with inter-agency coordination whose implementation refers to the applicable laws and regulations.